Β‐catenin regulates FOXP2 transcriptional activity via multiple binding sites. (26th December 2020) - Richter, Gesa; Gui, Tianshu; Bourgeois, Benjamin; Koyani, Chintan N.; Ulz, Peter; Heitzer, Ellen; von Lewinski, Dirk; Burgering, Boudewijn M. T.; Malle, Ernst; Madl, Tobias
Abstract : The transcription factor forkhead box protein P2 (FOXP2) is a highly conserved key regulator of embryonal development. The molecular mechanisms of how FOXP2 regulates embryonal development, however, remain elusive. Using RNA sequencing, we identified the Wnt signaling pathway as key target of FOXP2‐dependent transcriptional regulation. Using cell‐based assays, we show that FOXP2 transcriptional activity is regulated by the Wnt coregulator β‐catenin and that β‐catenin contacts multiple regions within FOXP2. Using nuclear magnetic resonance spectroscopy, we uncovered the molecular details of these interactions. β‐catenin contacts a disordered FOXP2 region with α‐helical propensity via its folded armadillo domain, whereas the intrinsically disordered β‐catenin N terminus and C terminus bind to the conserved FOXP2 DNA‐binding domain. Using RNA sequencing, we confirmed that β‐catenin indeed regulates transcriptional activity of FOXP2 and that the FOXP2 α‐helical motif acts as a key regulatory element of FOXP2 transcriptional activity. Taken together, our findings provide first insight into novel regulatory interactions and help to understand the intricate mechanisms of FOXP2 function and (mis)‐regulation in embryonal development and human diseases. Database: Expression data are available in the GEO database under the accession number GSE138938 . Abstract : When the Wnt pathway is off duty, the transcription factor FOXP2 can up‐ and downregulate the transcription of a set of genes including Wnt‐related targets. Upon activation of the Wnt pathway, β‐catenin via direct interaction with FOXP2 can modulate its transcriptional activity in a TCF/LEF‐dependent and/or TCF/LEF‐independent manner.